2013
DOI: 10.1242/jcs.121244
|View full text |Cite
|
Sign up to set email alerts
|

Mcp1 and Mcp2, two novel proteins involved in mitochondrial lipid homeostasis

Abstract: SummaryThe yeast mitochondrial outer membrane (MOM) protein Mdm10 is involved in at least three different processes: (1) association of mitochondria with the endoplasmic reticulum and mitochondrial lipid homeostasis (2) membrane assembly of MOM proteins, and (3) inheritance and morphogenesis of mitochondria. To decipher the precise role of Mdm10 in mitochondrial function, we screened for high-copy suppressors of the severe growth defect of the mdm10D mutant. We identified two novel mitochondrial proteins (open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(132 citation statements)
references
References 74 publications
9
122
1
Order By: Relevance
“…Multicopy extragenic suppressors of phenotypes associated with loss of ERMES components have recently been identified (104). Specifically, a multicopy suppressor screen for genes whose increased dose could restore growth of mdm10 cells on a nonfermentable carbon source at 37°C led to the isolation of two mitochondrial proteins, Mdm10 complementing protein (Mcp)1 and Mcp2 (104).…”
Section: Mitochondrial Connections Beyond Ermesmentioning
confidence: 99%
See 2 more Smart Citations
“…Multicopy extragenic suppressors of phenotypes associated with loss of ERMES components have recently been identified (104). Specifically, a multicopy suppressor screen for genes whose increased dose could restore growth of mdm10 cells on a nonfermentable carbon source at 37°C led to the isolation of two mitochondrial proteins, Mdm10 complementing protein (Mcp)1 and Mcp2 (104).…”
Section: Mitochondrial Connections Beyond Ermesmentioning
confidence: 99%
“…Specifically, a multicopy suppressor screen for genes whose increased dose could restore growth of mdm10 cells on a nonfermentable carbon source at 37°C led to the isolation of two mitochondrial proteins, Mdm10 complementing protein (Mcp)1 and Mcp2 (104). The overexpression of these proteins reverted the globular mitochondrial morphology of mdm10 ERMES core complex, Mdm10, is a mitochondrial -barrel protein.…”
Section: Mitochondrial Connections Beyond Ermesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, sterols are an additional group of lipids that might be transferred through the ER-mitochondria contact site. In support of this notion, loss of ERMES components Mdm10, Mdm12 or Mmm1 resulted in an increase of mitochondrial ergosterol levels, suggesting a connection between this contact site and ergosterol transfer to or from mitochondria [19]. Indeed, Lam6, which is localized to ERMES contact sites, was suggested to have a role in sterol transfer between the two organelles, as it was able to extract sterols from membranes [14,15].…”
Section: Introductionmentioning
confidence: 78%
“…It has been reported that yeast cells lacking the ERMES complex have reduced ergosterol levels in mitochondria, pointing to a role of ER-mitochondria contacts for ergosterol exchange (Tan et al, 2013). Non-vesicular transport of cholesterol mediated by protein-protein interactions between lipid droplets and mitochondria has been observed in steroidogenic cells (Boström et al, 2007;Goodman, 2008;Murphy et al, 2009;Zehmer et al, 2009), but it remains unknown how contacts between lipid droplets and mitochondria are maintained.…”
Section: Cholesterol Transport To Mitochondriamentioning
confidence: 99%